Historical analysis of PAI-1 from its discovery to its potential role in cell motility and disease - Dellas, Claudia; Loskutoff, David J. (Thrombosis and Haemostasis, 2005)
Although plasminogen activator inhibitor 1 (PAI-1) is one of the primary regulators of the fibrinolytic system, it also has dramatic effects on cell adhesion, detachment and migration. PAI-1 also differs from other serine protease inhibitors (serpins) in that it is a trace protein in plasma, it has a short half-life in vivo, its synthesis is highly regulated, and it binds to the adhesive glycoprotein vitronectin (VN) with high affinity and specificity. These unique and diverse properties of PAI-1 probably account for the many observations in the literature that correlate abnormalities in PAI-1 gene expression with a variety of pathological conditions. In this review, we discuss the discovery, origin, properties and regulation of PAI-1, and then speculate about its potential role in vascular disease, fibrosis, obesity and the metabolic syndrome, and cancer.
Keywords: PAI-1; vascular disease; fibrosis; obesity; cancer